Preventing, mitigating, and managing future pandemics for people with an intellectual and developmental disability ‐ Learnings from COVID‐19: A scoping review. Issue 1 (22nd January 2022) - Taggart, Laurence; Mulhall, Peter; Kelly, Rosie; Trip, Henrietta; Sullivan, Bill; Wallén, Eva Flygare
Abstract: Many people with an intellectual and developmental disability (IDD) are biologically, socially, and economically/politically vulnerable to developing SARS‐COV‐2 (COVID‐19) compared to the general population. Most governments have developed public‐health policies and strategies to address the challenges that COVID‐19 has presented. These policies and strategies have been based upon the general population and in fact could be detrimental to the health and well‐being of people with IDD. This paper provides a review of the key learning points emerging from the COVID‐19 literature, together with guidance for the provision of services and government interventions for people with an IDD for future pandemics. Using guidance from the Joanna Briggs Institute, a scoping review was used to explore the current literature (scientific and grey) on IDD and COVID‐19. Three core themes emerged from the review. Prevention/protection : User‐friendly accurate accessible information, handwashing and social distancing, Personal Protective Equipment, shielding, track and trace, testing, vaccine compliance/hesitancy, and training. Mitigation : Making reasonable adjustments both to where people live, and to community healthcare/clinical practice; and the use of technology as a pandemic‐response strategy. Treatment/Management : Access to acute hospitals and lifesaving equipment, using a suitable clinical fatality assessment instrument, stopping Do Not Resuscitate notices, individualised care plans and hospital passports, family/paid carers to support people in hospitals; and use of telehealth in clinical care. This is the first international scoping review that provides a narrative synthesis of emerging themes related to the COVID‐19 pandemic and people with an IDD. This paper highlights themes related to preventing, mitigating, and treating/managing the care of this population during the COVID‐19 pandemic, which can inform future public‐health policies. This paper also exposes the negative impacts of public‐health interventions in both High‐Income Countries and Low‐Middle Income Countries for this population including lapses in upholding human rights. These data provide a basis for learning from the COVID‐19 pandemic in planning for future pandemics.